(untitled) (West African Journal on Sustainable Development, 2024)
Religion plays a significant role in shaping socio-cultural dynamics, particularly in countries like Nigeria where diverse religious beliefs coexist. This research article delves into the intricate relationship between religion and sustainable development in Nigeria, with a focus on promoting peace and well-being. Through a multidisciplinary approach, the study examines how religious beliefs, practices, and institutions influence various aspects of sustainable development, including economic growth, social cohesion, environmental stewardship, and human well-being. Drawing upon existing literature, empirical data, and case studies, the article explores both the positive and negative impacts of religion on sustainable development efforts in Nigeria. Furthermore, it investigates strategies for harnessing the potential of religious communities as catalysts for promoting peace, fostering social harmony, and advancing sustainable development goals. The findings of this research contribute to a deeper understanding of the complex interplay between religion and sustainable development, offering insights for policymakers, practitioners, and scholars seeking to leverage religious resources for the common good in Nigeria and beyond.